(RETRACTED) Taboo of Madura Women: Patriarchal Construction in Madurese Tradition - Dahniar Th. Musa; Rupita Rupita; Nikodemus Niko (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
Reason for Retraction (February 18th, 2022):This paper is retracted by the editors due to publication ethics misconduct by authors. The article is plagiarism from another author (plagiarism for authorship).